Case Report: Cord blood-derived natural killer cells as new potential immunotherapy drug for solid tumor: a case study for endometrial cancer - Mu, Yongxu; Tong, Jiabei; Wang, Yujun; Yang, Yuxiao; Wu, Xiaoyun (Frontiers in Immunology, 2023)
Adoptive transfer of natural killer (NK) cells represents a viable treatment method for patients with advanced malignancies. Our team previously developed a simple, safe, and cost-effective method for obtaining high yields of pure and functional NK cells from cord blood (CB) without the need for cell sorting, feeder cells, or multiple cytokines. We present the case of a 52-year-old female patient diagnosed with poorly differentiated stage ⅣB (T3N2M1) endometrial cancer, who exhibited leukemoid reaction and pretreatment thrombocytosis as paraneoplastic syndromes. The patient received two courses of CB-derived NK (CB-NK) cell immunotherapy between March and September 2022, due to her extremely low NK cell activity. Two available CB units matched at 8/10 HLA with KIR-mismatch were chosen, and we were able to produce NK cells with high yield (>1.0×10 10 NK cells), purity (>90%), and function (>80%) from CB without cell sorting, feeder cells, or multiple cytokines. These cells were then adoptively transferred to the patient. No adverse effects or graft-versus-host disease were observed after infusion of CB-NK cells. Our clinical experience supports the efficacy of CB-NK cell treatment in increasing NK cell activity, depleting tumor activity, improving quality of life, and reducing the size of abdominal and pelvic masses with the disappearance of multiple lymph node metastases through the regulation of systemic antitumor immunity. Remarkably, the white blood cell and platelet counts decreased to normal levels after CB-NK cell immunotherapy. This clinical work suggests that CB-NK cell immunotherapy holds promise as a therapeutic approach for endometrial cancer.